Angular leaf spot - Correa Victoria, Fernando J.; Pastor Corrales, Marcial A.; Saettler, A.W. (International Center for Tropical Agriculture, 1989)
Angular leaf spot, caused by the fungus Isariopsis griseola in tropical and subtropical regions, can cause losses up to 50 percent. The pathogen infects the leaves by entering through the stomata or can be transmitted by the seed. Disease control can be carried out by cultural practices, use of disease-free seeds, planting in well-drained soils, the removal of infected harvest debris, and the utilization of chemical products and resistant var. Color illustrations are given of the symptoms and damage caused by the disease. (CIAT)